2016
DOI: 10.1002/cbic.201600469
|View full text |Cite
|
Sign up to set email alerts
|

A Second, Druggable Binding Site in UDP‐Galactopyranose Mutase from Mycobacterium tuberculosis?

Abstract: UDP-galactopyranose mutase (UGM), a key enzyme in the biosynthesis of mycobacterial cell walls, is a potential target for the treatment of tuberculosis. In this work, we investigate binding models of a non-substrate-like inhibitor, MS-208, with M. tuberculosis UGM. Initial saturation transfer difference (STD) NMR experiments indicated a lack of direct competition between MS-208 and the enzyme substrate, and subsequent kinetic assays showed mixed inhibition. We thus hypothesized that MS-208 binds at an alloster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…These two different resultss uggest two possible behaviors of 4 as aU GM inhibitor.E ither it acts as ac ompetitive inhibitor ( 29) > 1000 > 100 7ombuin (31) > 1000 > 100…”
Section: Study Of the Bindingmode Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…These two different resultss uggest two possible behaviors of 4 as aU GM inhibitor.E ither it acts as ac ompetitive inhibitor ( 29) > 1000 > 100 7ombuin (31) > 1000 > 100…”
Section: Study Of the Bindingmode Ofmentioning
confidence: 99%
“…This potential allosterics ite has recently been study by Pinto et al [31] They described, through docking calculations, saturation transfer difference (STD) NMR spectroscopy,a nd mutagenesis, the potentialb inding of am ixed inhibitori nt his second pocket of the opened form of Mt UGM. It has therefore been proposed that binding of this allosterics ite would induce am ajor structuralm odification of the substrate actives ite, preventinge nzyme turnover ( Figure 5).…”
Section: Study Of the Bindingmode Ofmentioning
confidence: 99%
“…Specifically, a small-molecule heterocycle (MS-208) that differs in structure from the inhibitors described herein was reported to inhibit MtUGM ( K i ∼400 μM). 32 The kinetics of inhibition together with computational and mutagenesis studies suggested that MS-208 does not compete directly with the substrate UDP-Gal p but rather binds in an allosteric site. The presence of multiple subsites highlights the flexibility of UGM.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitor trapping of UGM in an inactive conformation could be an effective inhibition strategy. 32 Indeed, many kinase inhibitors bind to and stabilize an inactive conformation of their target enzymes 53-56 . Our data thus far suggest inhibitors that can occupy the closed, oxidized state of the enzyme might be especially effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation